LAYANAN BIMBINGAN BELAJAR BERBASIS REMEDIAL TEACHING UNTUK MEMBANTU SISWA SLOW LEARNER DALAM MEMBACA - Safitri, Meliza Rika; Nurina, Putri; Hsb, Fitri Husaibatul Khairat (Jurnal Manajemen Pendidikan, 2025)
Reading ability is one of the important things that support student success at school. Slow learner students are individuals who experience barriers to learning. This study aims to describe remedial teaching-based tutoring services to help slow learner students in reading. This research uses a case study method with a sample of 1 student named F, a slow learner student in Junior High School (SMP), who has conducted a psychological examination with the results of IQ = 85, which is a category below average. Data analysis uses qualitative through the provision of remedial teaching-based tutoring services, students who experience slow learners usually have difficulty recognizing word structures and interpreting them. Remedial teaching-based tutoring services are remedial learning presented to slow learner students. Remedial teaching-based tutoring services are expected to be able to improve reading skills for slow learner students. Based on the results of the research, the provision of remedial teaching-based tutoring services for slow learner students and using observation questionnaires for the development of children's reading skills, shows that there is an increase in reading skills which is reflected in increased understanding, and the ability to read text. So from the results obtained, it can be concluded that remedial teaching-based tutoring services show an increase in reading skills in slow learner students